Guideline for Diagnosis and Treatment of Neurogenic Bowel Dysfunction with Traditional Chinese Medicine - LENG Jun; LI Li; YU Shaohong; MENG Xiangxia; YAN Tinghua; LI Benyuan; YUE Zenghui; BI Hongyan; CHANG Guangzhe; CHEN Bin; LI Yanhui; YANG Rong (康复学报)
Neurogenic bowel dysfunction (NBD) is one of the common complications of stroke and spinal cord injury. Traditional Chinese medicine (TCM) has a long history of diagnosis and treatment. In recent years, it has been increasingly applied in the treatment of NBD and achieved greate therapeutic effect. In order to standardize the diagnosis and treatment of NBD in China and to ensure the standardization of TCM diagnosis and treatment, this guideline is formulated based on the research achievements of TCM prevention and treatment of NBD at home and abroad. Drawing on the principles and methods for developing evidence-based medical guidelines, it establishes an evidence grading system through literature retrieval and screening, literature evaluation and grading, and literature quality assessment. Expert consultation and validation are conducted, and the guideline is revised according to expert opinions. This guideline has standardized and formulated specific contents such as the definition, diagnosis, TCM syndrome differentiation, treatment, efficacy evaluation of NBD, which has been approved and released by Shandong Standardization Association (Standard No.T/SDAS866-2024). It is of great significance in guiding clinical staff and rehabilitation therapists to use TCM in diagnosis and treatment of NBD and improving its prognosis, as well as in promoting its application.